An overview of the role of information technology in strategic management: Part I. (12th May 2004) - Galbreath, Jeremy
Strategic management encompasses the broad-based factors of strategy formulation and strategy implementation. Historically, much of strategic management's influences came from an Industrial Age "mindset" including concepts and management philosophies. However, economic change now appears to be a foregone conclusion. Indeed, many suggest that the structure of global business is in the middle of a so-called "new economy" transformation to the Information or Knowledge Age, one where the association between a new economic order and information technology is often made. Unfortunately, while strategic management has been widely discussed in the literature, discussions have seemingly fallen short when taken in context with information technology. The argument is made that information technology is indeed essential to the processes of strategic management and should take on more substantive discussions in the literature.